2021
DOI: 10.3389/fmicb.2021.639997
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Specific Root Microbiome of the Hyperaccumulator Noccaea brachypetala Growing in Non-metalliferous Soils

Abstract: Noccaea brachypetala is a close relative of Noccaea caerulescens, a model plant species used in metal hyperaccumulation studies. In a previous survey in the Catalan Pyrenees, we found two occidental and two oriental N. brachypetala populations growing on non-metalliferous soils, with accumulated high concentrations of Cd and Zn. Our hypothesis was that the microbiome companion of the plant roots may influence the ability of these plants to absorb metals. We performed high-throughput sequencing of the bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…For the shoots of S. nigrum, the increasing levels of Mo stimulated Cd accumulation for both MoO 3 NPs and Mo 6+ treatments, where the highest Cd concentration was observed at 34.06 ± 6.88 mg kg −1 in the NP-40 group, followed by 29.06 ± 4.98 mg kg −1 in the I-40 group compared to CK (11.96 ± 2.30 mg kg −1 ), while for the plant roots, Cd concentrations (7.10 ± 0.47 mg kg −1 in CK) climbed to 36.89 ± 4.59 and 32.28 Nevertheless, excessive Mo amendment jeopardized the homeostasis of heavy-metal translocation and normal functioning in vascular systems, which contribute to excessive accumulation of nonessential elements (as indicated by the Cd, As, and Pb contents displayed in Table S3) in S. nigrum shoots for the NP/I-40 groups compared to CK (p < 0.05). 50 Similar to plant growth, MoO 3 NPs also exhibited stronger stimulation in Cd uptake of S. nigrum than that exhibited by ion treatment under the same dose.…”
Section: Metal Accumulation and Nutrient Uptakementioning
confidence: 80%
See 1 more Smart Citation
“…For the shoots of S. nigrum, the increasing levels of Mo stimulated Cd accumulation for both MoO 3 NPs and Mo 6+ treatments, where the highest Cd concentration was observed at 34.06 ± 6.88 mg kg −1 in the NP-40 group, followed by 29.06 ± 4.98 mg kg −1 in the I-40 group compared to CK (11.96 ± 2.30 mg kg −1 ), while for the plant roots, Cd concentrations (7.10 ± 0.47 mg kg −1 in CK) climbed to 36.89 ± 4.59 and 32.28 Nevertheless, excessive Mo amendment jeopardized the homeostasis of heavy-metal translocation and normal functioning in vascular systems, which contribute to excessive accumulation of nonessential elements (as indicated by the Cd, As, and Pb contents displayed in Table S3) in S. nigrum shoots for the NP/I-40 groups compared to CK (p < 0.05). 50 Similar to plant growth, MoO 3 NPs also exhibited stronger stimulation in Cd uptake of S. nigrum than that exhibited by ion treatment under the same dose.…”
Section: Metal Accumulation and Nutrient Uptakementioning
confidence: 80%
“…In the present study, we observed that the application of micronutrient Mo materials significantly stimulated Cd uptake by the root tissue of S. nigrum , and the transport of Cd to the above-ground part was to avoid root damage by excessive Cd accumulation. Nevertheless, excessive Mo amendment jeopardized the homeostasis of heavy-metal translocation and normal functioning in vascular systems, which contribute to excessive accumulation of nonessential elements (as indicated by the Cd, As, and Pb contents displayed in Table S3) in S. nigrum shoots for the NP/I-40 groups compared to CK ( p < 0.05) . Similar to plant growth, MoO 3 NPs also exhibited stronger stimulation in Cd uptake of S. nigrum than that exhibited by ion treatment under the same dose.…”
Section: Resultsmentioning
confidence: 99%
“…It is also occasionally explicit in, e.g., studies of root‐associated microbiota (e.g. Martos et al., 2021 ). At least as understood in social sciences, this frame does not necessarily stem from an ecological framework or rest on ecological assumptions.…”
Section: Resultsmentioning
confidence: 99%